Pelatihan Pengolahan Minyak Jelantah Menjadi Lilin Aromaterapi untuk Pemberdayaan Masyarakat Desa Sudipayung Kendal: Penelitian - Yeni Tri Hidayati; Ela Kurniasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The issue of used cooking oil waste in households is often overlooked, even though its repeated use can be harmful to health and its disposal without proper management can pollute the environment. In Sudipayung Village, many residents still dispose of used cooking oil without proper management, so education and innovation in its utilization are needed. This activity aims to increase the understanding of PKK members and housewives about the dangers of used cooking oil and provide them with the skills to process it into aromatherapy candles that have economic potential. The methods used include socialization on household waste management, especially used cooking oil, and hands-on training in making aromatherapy candles. The results of the activity showed that participants were enthusiastic, understood the material presented, and were able to make aromatherapy candles independently. The conclusion of this activity is that participants' knowledge and skills in utilizing used cooking oil into useful products have increased, thereby becoming an alternative home business that supports community empowerment.